2019
DOI: 10.5515/kjkiees.2019.30.4.314
|View full text |Cite
|
Sign up to set email alerts
|

W-Band Radar Altimeter for Drones

Abstract: In this study, we propose a W-band frequency modulated continuous wave(FMCW) radar altimeter that can measure the altitude based on the frequency differences of transmitted and received signals. This W-band FMCW system is powered by an altitude control algorithm, which we propose to help prevent collisions of drones with obstacles in real deployment by measuring the relative altitude. It is shown that this algorithm enables the drone to be positioned within a 3 % error of altitude from the desired input height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 6 publications
(2 reference statements)
2
3
0
Order By: Relevance
“…Lee et al reported that, in their experiments, doping Ti into amorphous LiPON enhanced Li + ionic conductivity, 17 quite consistent with our theoretical calculations on the effect of Ti-doping on the ionic conductivity. However, due to the poor energetic stability of Ti-doped LiPON, compared to that of undoped LiPON, more rapid formation of secondary phases and worse cyclability (shorter lifetime) were expected.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Lee et al reported that, in their experiments, doping Ti into amorphous LiPON enhanced Li + ionic conductivity, 17 quite consistent with our theoretical calculations on the effect of Ti-doping on the ionic conductivity. However, due to the poor energetic stability of Ti-doped LiPON, compared to that of undoped LiPON, more rapid formation of secondary phases and worse cyclability (shorter lifetime) were expected.…”
Section: Resultssupporting
confidence: 92%
“…However, all the doping elements considered in this study were indicated to reduce the LiPON crystal unit cell volume-but, interestingly, to increase the amorphous LiPON cell volume, indicating the ability of the dopants to enhance the Li ion conductivity. Lee et al reported that, in their experiments, doping Ti into amorphous LiPON enhanced Li + ionic conductivity, 17 quite consistent with our theoretical calculations on the effect of Tidoping on the ionic conductivity. However, due to the poor energetic stability of Ti-doped LiPON, compared to that of undoped LiPON, more rapid formation of secondary phases and worse cyclability (shorter lifetime) were expected.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations